2020
DOI: 10.1126/scitranslmed.aax1798
|View full text |Cite
|
Sign up to set email alerts
|

PBX1 expression in uterine natural killer cells drives fetal growth

Abstract: Abundant decidual natural killer (dNK) cells at the maternal-fetal interface are important during early pregnancy. However, functional subsets of dNK cells remain poorly understood. We describe a CD49a+PBX homeobox 1 (PBX1)+ dNK cell subset that promotes fetal development in humans and mice. The expression of PBX1 in dNK cells is up-regulated via the activated AKT1 pathway through the interaction of major histocompatibility complex G with the immunoglobulin-like transcript 2 receptor. PBX1 drives pleiotrophin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Here, we present single-cell transcriptomes of the decidual immune microenvironment in patients with RPL. We identified that RPL patients have a remarkably decreased number of a particular subset of dNK cells (dNK1), which may contribute to the secretion of growth-promoting factors to promote normal pregnancy 38 . Meanwhile, RPL patients harbor significantly increased numbers of a proinflammatory subset of dNK cells (dNK3) that produce cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present single-cell transcriptomes of the decidual immune microenvironment in patients with RPL. We identified that RPL patients have a remarkably decreased number of a particular subset of dNK cells (dNK1), which may contribute to the secretion of growth-promoting factors to promote normal pregnancy 38 . Meanwhile, RPL patients harbor significantly increased numbers of a proinflammatory subset of dNK cells (dNK3) that produce cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal Lin − NKp46 + NK1.1 + cells consist of Eomes + RORγt-fate map − cNK cells, which express CD27 and lack IL-7Rα, along with a smaller fraction of Eomes − RORγt-fate map + NK cells [ 103 ] that is similar to liver-resident NK cells [ 104 ]. Thus, cNK and trNK cells significantly differ in their requirement of the developmental niche and transcriptional networks [ 105 , 106 ]. The topological organization of trNK cells within the microenvironment in organs such as lung or uterus holds clues about their functions, interacting partners, and cellular signals [ 107 , 108 , 109 , 110 ].…”
Section: Cnk Versus Trnk Cellsmentioning
confidence: 99%
“…The CD11b-CD27-property of dNKc manifests their immature characteristic and the potential to differentiate (Fu et al, 2011). Specific expression of PBX1 was found in CD27-CD11b-dNK cells, and a recent study demonstrated the association of decreased PBX1 expression or PBX1 G21S mutation with unexplained RSA (Zhou et al, 2020), further suggesting the crucial role of this dNK subset in pregnancy maintenance. Interestingly, a recently identified pregnancy trained dNK (PTdNK) share similar features with dNKc or dNK1 (Gamliel et al, 2018b), and this subset has been speculated to be enriched and boost decidua receptivity in subsequent pregnancy, therefore may be responsible for the "memory" of reproductive outcomes in next pregnancies.…”
Section: Comparison Of the Differential Gene Expression In Dnk Subsetmentioning
confidence: 90%